Sensitivity to change and responsiveness of the Stroke and Aphasia Quality-of-Life Scale (SAQOL) in a Singapore stroke population. Issue 4 (3rd April 2017) - Guo, Yiting Emily; Togher, Leanne; Power, Emma; Heard, Rob; Luo, Nan; Yap, Philip; Koh, Gerald C. H.
ABSTRACT: Background : The health-related quality of life (HRQoL) of people with aphasia (PWA) in Singapore is unknown. Aims : To compare outcomes between stroke survivors with and without aphasia in Singapore and examine the sensitivity and responsiveness to change of the Stroke and Aphasia QOL Scale (SAQOL-39g) and its Singapore (Mandarin) variant, SAQOL-CSg. Methods & Procedures : A longitudinal cohort study was conducted with stroke survivors with and without aphasia. Participants underwent a series of questionnaires at 3 and 12 months post-stroke including SAQOL-39g/SAQOL-CSg, Barthel Index, Modified Rankin Scale (MRS), Mini Mental State Examination, Frontal Assessment Battery, Center for Epidemiologic Studies Depression Scale and the EQ-5D. The following data analyses were conducted: comparison of stroke outcomes between participants with and without aphasia, computation of floor and ceiling effects, calculation of effect sizes (ESs) to determine sensitivity to change and estimation of minimally important differences (MIDs) for examining responsiveness. Outcomes & Results : A total of 78 participants (29.5% female, 29.5% PWA, mean age 64.1 years) completed all the assessments on both occasions. At 12 months post-stroke, PWA had higher levels of disability on the MRS (Mann–Whitney U = 294.5, p < 0.01) and reported significantly lower quality of life on the SAQOL-39g/SAQOL-CSg ( U = 349, p < 0.01) and the EQ-5D index ( U = 447, p < 0.05). In terms of sensitivity to change, the SAQOL-39g/SAQOL- 35CSg showed a small degree of improvement for the entire sample (ES, r = 0.22) but change was only significant for participants without aphasia. MID estimates for improvement were 0.21 on the SAQOL-39g/SAQOL-CSg and 0.17 on the EQ-5D index. Conclusions : PWA reported poorer HRQoL even when physical function was comparable. SAQOL-39g/SAQOL-CSg was found to have adequate sensitivity to change (i.e., reflect at least small change) up to 12 months post-stroke. MID estimates of the SAQOL-39g/SAQOL-CSg may assist in the interpretation of changes in scores in the clinical setting.